A. M. Thornton, C. Iacobini, C. Burani: BDVDB -Una base di dati sul Vocabulario di Base della Lingua Italiana, Roma, Bulzoni, 1997. - Pérez Belló, Gloria (Cuadernos de Filología Italiana, 1998)
Sin resumen